Medijska etika in profesionalnost v digitalnem komunikacijskem okolju - Kerševan Smokvina, Tanja (Javnost (Ljubljana), 2021)
While the digitalization of the communication environment led to the situation of regulatory imbalance between regulated and financially underfunded media on the one hand and unregulated and economically strong digital platforms on the other, citizens are receiving more and more information and media or media-like content through platforms. The aim of the study is to examine the responses of media self-regulatory bodies to issues of journalistic ethics and professionalism related to digitalization and the willingness of media self-regulatory bodies and statutory media regulators to co-regulate the digital communication environment. The analysis of codes of ethics and interviews with representatives of media self-regulatory bodies and media regulators from four countries on the territory of ex-Yugoslavia revealed similarities in the adaptation of media self-regulation to the problems of the digital communication environment but did not indicate common views on state intervention and on strengthened collaboration between media self-regulation bodies and media regulators.
Keywords: BiH; digitalne platforme; Hrvaška; Journalism ethics; Mass media; Množični mediji; Novinarska etika; novinarstvo; Profesionality; Profesionalnost; Slovenija; Srbija; zakonodaja